A Semantic Analysis on Online Apple Advertisements - Basri, Chusnil Wulandari (Politeknik Harapan Bangsa Surakarta, 2021)
This research is entitled A Semantic Analysis on Online Apple Advertisements. It is a study of the analysis of meaning in online advertisements contained on the official Apple website. The researchers examine the type of meaning and the function of associative meaning with the aim of finding its relationship with the company’s advertising and sales activities. This research uses descriptive qualitative as a research method. From this analysis, the researchers found 10 data that matched the research criteria and considered as the latest data to complete the research. Connotation becomes the most dominant type of meaning used. As for the function of speech whose meaning is adapted to the context of the ad sentence, assertive and expressive are the most commonly used because it displays facts succinctly. Keywords: advertisements, apple, types of meaning